Fever Among Pertussis Cases Reported Through Enhanced Pertussis Surveillance, 2015–2022 - Hughes, Michelle M; Rubis, Amy; Acosta, Anna M; Aden, Vanessa; Firmender, Patricia; Horn, Kate; Stanislawski, Emma; Wester, Rachel; Youngkin, Erin; Cruz, Victor; Skoff, Tami H (Open forum infectious diseases, 2025)
Fever is not considered a typical presentation of pertussis. We characterized fever among 7840 pertussis cases from the Centers for Disease Control and Prevention's Enhanced Pertussis Surveillance with cough onset from 2015 to 2022. Ten percent of cases had a reported fever. The presence of fever should not rule out pertussis as a cause of cough illness.